EFEKTIVITAS PIJAT REFLEKSI APIYU PADA KAKI TERHADAP PENURUNAN KADAR GULA DARAH PASIEN DIABETES MELLITUS TIPE 2 - Nurwindi " Madina; Yesi " Hasneli N; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to determine the effectiveness Apiyu on foot reflexology massage among diabetes mellitus type 2 patient’s blood glucose level. The design of this research was “Quasy experimental designed by “Non-equivalent control group”. The research was conducted by doing home visit to respondents at Arifin Achmad public hospital. The total sample were 30 respondents who fit the inclusion criteria and chosen by purposive sampling, which was divided into 15 respondents experiment group and 15 respondents control group. The experiment group was given Apiyu on foot reflexology massage on 30 minutes a day for three days consecutively and blood glucose level was checked when fasting minimum 8 hours before. Measuring instrument that used in both group was glucometer and observation  sheet. The analysis was used univariate analyzes to observed the respondents characteristics frequency and bivariate analyzes by using Dependent T-test and Independent T-test. The result of pre test and post test showed a decrease 9,8 of  mg/dl on the experiment group blood glucose level. The result of statistical test indicated a significant decrease on the experiment group with p value 0,000 (p<0,05). In conclusion, Apiyu reflexology massage are effective among diabetes mellitus type 2 patient’s blood glucose level decrease. The result is expected to be one of the nursing intervention to diabetes mellitus type 2 patient’s blood glucose level decrease. Keywords: Apiyu reflexology massage, blood glucose level, diabetes melitus type 2